Elephants et dissemination des graines de quelques espèces vegetales dans le Ranch de Gibier de Nazinga (sud du Burkina Faso) - Hien Mipro; Boussim Joseph; Guinko Sita (Pachyderm)
Seed dispersal by forest elephants was assessed from dung samples collected monthly July 1996-June 1997. Seeds contained in the dung piles were counted and natural germination was simulated. Seed densities varied significantly between months, with a maximum in April, suggesting that fruits replace green forage as the food supply for elephants during the dry season. The seeds collected at the beginning of the dry season germinated at a higher rate that those collected towards the end of the season. Elephants dispersed about 20% of the woody species at various habitats of the study area. Results illustrate that elephant feed on fruits mainly during the dry season, and that they play an important role in disseminating seeds in the Nazinga area.